ALKALINE PHOSPHATASE LEVEL MEASUREMENT TO DIFFERENTIATE MILD AND SEVERE AGGRESSIVE PERIODONTITIS: PENGUKURAN TINGKAT ALKALIN FOSFATASE UNTUK MEMBEDAKAN PERIODONTITIS AGRESIF RINGAN DAN BERAT - Mustaqimah Dewi Nurul; Auerkari Elza Ibrahim (TALENTA, 2010)
Individuals with aggressive periodontitis (AP) can have a heritable risk factors related to the bacterial floras, immunological responses and leukocyte functions. This study aimed to characterize indicators and differences between the two subclasses of AP. A series of clinical parameters and full mouth dental radiographs was obtained from 27 consenting AP patients. After sampling of gingival crevicular fluid (GCF) and peripheral blood, the activity of alkaline phosphatase (ALP) was measured from GCF by enzymatic method. The proportion of lymphocyte subpopulations was measured from blood by flow cytometry, and titter of immunoglobulin G against Porphyromonas gingivalis (Pg) fimbriae was determined from serum by ELISA. The results classified the subjects into eight subjects with mild AP (AP1) and 19 subjects with severe AP (AP2). From all indicators tested, we concluded that the GCF ALP was the one which was 100% specific for AP2, though with 76.9% sensitivity and 77.8% accuracy; and that AP1 and AP2 are different types of early-onset periodontitis (EOP), of which AP1 does not progress into AP2.